Aberrant RON and MET Co-overexpression as Novel Prognostic Biomarkers of Shortened Patient Survival and Therapeutic Targets of Tyrosine Kinase Inhibitors in Pancreatic Cancer - Hu, Chen-Yu; Xu, Xiang-Ming; Hong, Bo; Wu, Zhi-Gang; Qian, Yun; Weng, Tian-Hao; Liu, Yi-Zhi; Tang, Tao-Ming; Wang, Ming-Hai; Yao, Hang-Ping (Frontiers in Oncology, 2019)
RON (recepteur d’origine nantais) and MET (hepatocyte growth factor receptor) are tyrosine kinase receptors. Various cancers have aberrant RON and MET expression and activation, which contribute to cancer cell proliferation, invasiveness and metastasis. Here, we explored RON and MET expression in pancreatic cancer and their relationship with overall survival (OS) time, and evaluated their significance as therapeutic targets of tyrosine kinase inhibitors in pancreatic cancer. We enrolled 227 patients with pancreatic cancer in the study. RON and MET expression was analyzed by immunohistochemical staining. Four human pancreatic cancer cell lines expressing variable levels of RON or MET and four MET superfamily inhibitors (BMS777607, PHA665752, INCB28060, Tivantinib) were used. The effect of the four tyrosine kinase inhibitors on cell viability, migration, and apoptosis were determined using cell viability, scratch wound healing, and Caspase-Glo 3/7 assays. Cellular signaling was analyzed by immunoprecipitation and western blotting. The therapeutic efficacy of the tyrosine kinase inhibitors was determined with mouse xenograft pancreatic cancer models in vivo. There was wide aberrant RON and MET expression in the cancer tissues. In 227 pancreatic cancer samples, 33% had RON overexpression, 41% had MET overexpression, and 15.4% had RON and MET co-overexpression. RON and MET expression were highly correlated. RON and MET expression levels were significantly related to OS. Patients with RON and MET co-overexpression had poorer OS. BMS777607 and PHA665752 inhibited pancreatic cancer cell viability and migration, and promoted apoptosis by inhibiting RON and MET phosphorylation and further inhibiting the downstream signaling pathways in vitro. They also inhibited tumor growth and further inhibited phosphorylated (phosphor)-RON and phospho-MET expression in the mouse xenograft models in vivo effectively. INCB28060, which inhibits the MET signaling pathway alone, was not effective. RON and MET can be important indicators of prognosis in pancreatic cancer. Tyrosine kinase inhibitors targeting RON and MET in pancreatic cancer are a novel and potential approach for pancreatic cancer therapy.